PENERAPAN MODEL-MODEL PENGEMBANGAN KURIKULUM DI SEKOLAH - Fatma Wati; Siti Kabariah; Adiyono Adiyono (ADIBA : JOURNAL OF EDUCATION, 2022)
Changes from time to time make curriculum changes change, adjusting to the times and the needs needed by students and educators. The models also vary for the sake of suitability of curriculum development in schools and their respective problems which are of course different. Because of that the school will always try to evaluate in order to get the desired models, according to the criteria. This article describes the notion of curriculum and several development models curriculum. The existence of educators cannot be separated from the curriculum because the teacher is the mediator between the curriculum and students. Teachers can be involved in curriculum development in two ways, namely as participants in the process or as users of curriculum products. We can find various models of curriculum development in schools.